Environmental Repercussions and the Economic Structure: An Input-Output Approach: A Comment - Flick, Warren A. (The Review of Economics and Statistics, 1974)
, and , Reply, Review (Federal Reserve Bank of St. Louis, Apr. 1969), 12-16. DeLeeuw, F., and J. Kalchbrenner, and Fiscal Actions: Test of Their Relative Importance in Economic Stabilization Comment, Review (Federal Reserve Bank of St. Louis, Apr. 1969), 6-11. Goldfeld, S., and A. Blinder, Some Implications of Stabilization Policy, Brookings Papers on Economic Activity (3:1972), 585-640. Gramlich, E., Usefulness of Monetary and Fiscal Policy as Discretionary Stabilization Tools, Jozurnal of Money, Credit and Banking, 3 (May 1971), 506-532. Guttentag, J., Strategy of Open-Market Operations, Quarterly Journal of Economics, 80 (Feb. 1966), 1-30. Hendershott, P., The Neutralized Money Stock: An Unbiased Measure of Reserve Policy Actions (Homewood, Ill.: Richard D. Irwin), 1968. Lombra, R. E., and R. G. Torto, Endogenous Reserve Open Market Operations in a Macro-Econometric Model: First Report. Presented at the Winter Meeting of the Econometric Society, 1971. and Federal Reserve 'Defensive' Behavior and the Reverse Causation Argument, Southern Economic Journal, 40 (July 1973), 4755, and Staff Economic Studies, no. 75 (Board of Governors of the Reserve System), 1972. Silber, W., St. Louis Equation: 'Democratic' and 'Republican' Versions and Other Experiments, this REVIEW, 53 (Nov. 1971), 362-367. Waud, R., and Fiscal Effects on Economic Activity. Presented at the Winter Meeting of the Econometric Society, 1972. Wood, J., A Model of Reserve Behavior, in George Horwich (ed.), Monetary Process and Policy (Homewood, Ill.: Richard D. Irwin), 1967, 135-166.